Weight stigma and media: An examination of the effect of advertising campaigns on weight bias, internalized weight bias, self-esteem, body image, and affect. (March 2021) - Selensky, Jennifer C.; Carels, Robert A.
Highlights: Media shapes attitudes and beliefs that contribute to weight stigma and body ideals. Body positive advertising campaigns increase acceptance of diverse body sizes. Thin ideal promoting advertising campaign increases dislike of heavier individuals. Self-esteem and mood improve after viewing AerieReal or Dove Real Beauty campaign. Women feel bad about themselves and their bodies after viewing Victoria's Secret campaign. Abstract: While some media perpetuate weight stigma and an ideal of thinness, certain advertising campaigns, such as Aerie Real and Dove Real Beauty, have attempted to promote body acceptance. The current study evaluated the influence of exposure to these campaigns on weight bias, internalized weight bias (IWB), self-esteem, body image, and affect relative to exposure to a campaign perpetuating the thin ideal and a documentary on weight stigma. 475 female participants were randomized to one of five conditions: Aerie, Dove, Victoria's Secret, an HBO documentary, or control (i.e., neutral video clip). Participants completed measures of weight bias, IWB, self-esteem, body image, and affect one week prior to and immediately after watching the assigned video clip. Results showed positive effects of the Aerie and Dove campaigns on women. While global measures of weight bias and IWB were unchanged, women who viewed the Dove and Aerie campaigns reported significantly improved self-esteem and positive affect. Further, women found the campaigns to have positive, uplifting, and empowering messages. Aerie's and Dove's acceptance-promoting advertising campaigns positively influenced self-esteem and mood, and they are potential tools for weight bias reduction. Advertisements and media have the potential to impact weight-based attitudes in society.